Factors influencing quality of life up to the 36th month follow-up after treatment of acute coronary syndrome by coronary angioplasty - Uchmanowicz I; Łoboz-Grudzień K (Dove Medical Press, 2015)
Izabella Uchmanowicz,1 Krystyna Łoboz-Grudzień1,2 1Department of Clinical Nursing, Public Health Department, Wroclaw Medical University, Wroclaw, Poland; 2Department of Cardiology, T Marciniak Memorial Hospital, Wroclaw, Poland Purpose: Patients with acute coronary syndrome (ACS) constitute a very diverse group in terms of the severity and course of the disease, pharmacotherapy applied, and effort tolerance. Moreover, medical diagnosis is not always accompanied by patients’ subjective assessment of their health status and health-related quality of life (HRQOL). Hence, the objectives of this paper are as follows: i) to compare HRQOL of patients receiving percutaneous coronary intervention (PCI); ii) to detect whether depressive symptoms and the level of anxiety have an influence on the HRQOL; iii) to determine the dynamics of changes in the HRQOL of patients after PCI; and iv) to find any differences in the HRQOL of patients along lines of sex. Patients and methods: The study involved 90 patients (55 men, 35 women) aged 39–84 hospitalized due to ACS and who qualified for coronary angioplasty. HRQOL was measured using the Medical Outcomes Study 36-item Short-Form Survey, and analysis of depressive symptoms was performed using the Beck Depression Inventory. The level of anxiety was determined using modified State-Trait Anxiety Inventory. Results: Analyses of the dynamics of changes in the physical and mental domains revealed an unfavorable trend in the 36th month after surgery. The dynamics of change in the severity of depressive symptoms according to the Beck Depression Inventory showed an increase from 4.6 in the first week to 10.4 points in the 36th month. Changes in the levels of anxiety as a state and anxiety as a trait showed an unfavorable trend. Conclusion: The results of the study showed that more attention should be paid to anxiety accompanying cardiovascular diseases. There is a relationship between HRQOL and such variables as sex, age, anxiety and depressive symptoms. The results suggest that more attention should be focused on the distant quality of life of ACS patients after PCI. Keywords: acute coronary syndrome, quality of life, percutaneous coronary interventions